Compressão aguda de cauda equina por cisto sinovial inflamatório - Relato de caso - MARLON FERREIRA SANTOS; TÉOFILO DORNELES CLARO DOS SANTOS SILVA; RONAN LACERDA BARBOSA; FELIPE RODRIGUES DE CARVALHO; LAÍS DOS SANTOS PIMENTEL; EDEM MOURA DE MATOS JUNIOR (UniEVANGÉLICA, 2018)
Objective: To report a rare root cause of spinal compression evidencing the clinical complications as well as the therapeutic proposal. Case description: 78-year-old man, with no comorbidities, active, who developed a bilateral lumbosciatalgia and gait difficulties. Magnetic resonance imaging of the lumbar spine revealed an intra-articular nodule compressing the left posterior and lateral aspect of the dural sac at the L4-L5 level. Due to the rapid worsening of neurological symptoms, laminectomy was performed with surgical excision of the nodule and decompression of the horse's tail. Biopsy of the nodule evidenced the presence of inflammatory tissue. Comments: Although rare, lumbar synovial cysts may result in compression of the spinal structures. MRI is the imaging exam of choice to diagnose them, in addition to providing for the exclusion of other causes. The prognosis is favorable if the therapeutic course is taken swiftly and appropriately.